Nutritional Management of Patients With Enterocutaneous Fistulas: Practice and Progression - Tang, Qin-qing; Hong, Zhi-wu; Ren, Hua-jian; Wu, Lei; Wang, Ge-fei; Gu, Guo-sheng; Chen, Jun; Zheng, Tao; Wu, Xiu-wen; Ren, Jian-an; Li, Jie-shou (Frontiers in Nutrition, 2020)
The management of enterocutaneous fistulas (ECF) can be challenging because of massive fluid loss, which can lead to electrolyte imbalance, severe dehydration, malnutrition and sepsis. Nutritional support plays a key role in the management and successful closure of ECF. The principle of nutritional support for patients with ECF should be giving enteral nutrition (EN) priority, supplemented by parenteral nutrition if necessary. Although total parenteral nutrition (TPN) may be indicated, use of enteral feeding should be advocated as early as possible if patients are tolerant to it, which can protect gut mucosal barrier and prevent bacterial translocation. A variety of methods of enteral nutrition have been developed such as fistuloclysis and relay perfusion. ECF can also be occluded by special devices and then EN can be implemented, including fibrin glue application, Over-The-Scope Clip placement and three-dimensional (3D)-printed patient-personalized fistula stent implantation. However, those above should not be conducted in acute fistulas, because tissues are edematous and perforation could easily occur.